Rural Colombian College Students’ Motivations to Participate in an International Agricultural Internship - Carlos Alberto Parra Salinas; Neil A Knobloch (Journal of International Agricultural and Extension Education, 2025)
This qualitative study explored rural students' motivations to participate in agricultural study abroad. Thirty-five undergraduate students (24 women and 11 men) applied to participate in a 6-month cohort internship program through the application form and statement of purpose. The analysis of this information allowed us to identify the motivations of rural students to apply to a cohort internship program that offer possibilities of international exchange at a large university in the U.S. Four motivational categories to participate in the study abroad were described (i.e., academic, personal, career, and community motivations). Practical implications are provided for government and university administrators and program coordinators with rural youth motivation information to help them plan their internationalization efforts for academic exchanges.
Keywords: Colombian youth; rural education; study abroad; student expectations; student motivation